Professionalism Training For Surgical Residents: Documenting the Advantages of a Professionalism Curriculum. Issue 3 (September 2016) - Hochberg, Mark S.; Berman, Russell S.; Kalet, Adina L.; Zabar, Sondra; Gillespie, Colleen; Pachter, H. Leon
Abstract : Objectives: Professionalism education is a vital component of surgical training. This research attempts to determine whether an annual, year-long professionalism curriculum in a large surgical residency can effectively change professionalism attitudes. Summary of Background Data: The ACGME mandated 6 competencies in 2003. The competencies of Professionalism and Interpersonal/Professional Communication Skills had never been formally addressed in surgical resident education in the past. Methods: A professionalism curriculum was developed focusing on specific resident professionalism challenges: admitting mistakes, effective communication with colleagues at all levels, delivering the news of an unexpected death, interdisciplinary challenges of working as a team, the cultural challenge of obtaining informed consent through an interpreter, and the stress of surgical practice on you and your family. These professionalism skills were then evaluated with a 6-station Objective Structured Clinical Examination (OSCE). Identical OSCE scenarios were administered to 2 cohorts of surgical residents: in 2007 (before instituting the professionalism curriculum in 2008) and again in 2014. Surgical residents were rated by trained Standardized Patients according to a behaviorally anchored professionalism criteria checklist. Results: An analysis of variance was conducted of overall OSCE professionalism scores (% well done) as the dependent variable for the 2 resident cohorts (2007 vs 2014). The 2007 residents received a mean score of 38% of professionalism items "well done" (SD 9%) and the 2014 residents received a mean 59% "well done" (SD 8%). This difference is significant ( F = 49.01, P  < .001). Conclusions: Professionalism education has improved surgical resident understanding, awareness, and practice of professionalism in a statistically significant manner from 2007 to 2014. This documented improvement in OSCE performance reflects the value of a professionalism curriculum in the care of the patients we seek to serve.